Differential Bottom‐Up Control of Planktonic and Sedimentary Bacterial Communities by Phytoplankton and Extracellular Enzymes in an Asymmetric River Confluence - Yi Li; Huijuan Huang; Bi Luo; Rong Wang; Bing Yu; Xian Xu; Zhaotong Chen; Yushan Li; Zhiwei Zhu (Molecular Ecology, 2026)
Bacterial community dynamics underlie ecosystem functioning in river networks, yet how different bacterial lifestyles respond to bottom‐up biotic drivers under confluence‐induced hydraulics remains unclear. Here, we quantified spatial heterogeneity in free‐living (FL), particle‐associated (PA) and sedimentary (S) bacterial assemblages, coupled with phytoplankton and extracellular enzyme profiles, at the Yellow River‐Fenhe River confluence during the summer wet season. Clear habitat partitioning emerged, with stronger divergence at the water–sediment interface than between the two planktonic fractions (FL vs. PA). Hydrological source tracking showed that Fenhe River‐derived taxa dominated both water and sediment within the confluence reaches, whereas Yellow River lineages prevailed in the downstream reaches. Community assembly shifted hierarchically: homogeneous selection dominated FL assemblages but declined progressively toward PA and sedimentary fractions, while dispersal limitation intensified in tandem with niche contraction. Multivariate analyses showed that in addition to physicochemical factors, enzyme activity is the strongest factor predicting FL communities, explaining 43.6% of variability, whereas the phytoplankton community best predicted PA communities (68.8%). Sedimentary communities correlated weakly with phytoplankton associations (21.8%) and showed no significant link with enzyme activity. Our findings identify phytoplankton communities and enzymatic potential as key bottom‐up drivers whose relative importance varies with bacterial lifestyle, providing mechanistic insight into biophysical dynamics within river‐confluence ecosystems.

Male and Female Parent Birds Enhance Their Reproductive Success Using Different Strategies but the Same Optimal Pathway - Ning‐Ning Sun; Bi‐Yun Jia; Rong‐Yu Xu; Li‐Fang Gao; Xue‐Fei Guo; Rang Li; Yu‐Jie Wang; Shu‐Min Wang; Bo Du (Molecular Ecology, 2025)
Parental birds exhibit diverse alternative reproductive strategies; however, the pathways by which these alternative strategies enhance the reproductive success of parents remain poorly understood. Here, we used generalised linear mixed models (GLMMs) and structural equation modelling (SEM) to analyse a long‐term dataset of multiple components of reproductive fitness in the azure‐winged magpie ( Cyanopica cyanus ), including incipient offspring number, extra‐pair fertilisation (EPF), unhatched eggs, offspring preyed on by predators and conspecific raiders and offspring that starved. GLMM results revealed significant associations between these components and the first lay date. SEM further elucidated causal relationships among female/male breeding conditions, cooperative breeding, first lay date and the positive/negative effects on female/male reproductive success. SEM results revealed that both female and male reproductive success were mainly influenced by negative effects rather than positive effects. Specifically, negative effects were largely determined by unhatched eggs for females but by female EPF frequency for males. In contrast, positive effects were predominantly determined by the incipient offspring number for both sexes. Therefore, minimising negative effects was prioritised over enhancing positive effects to achieve reproductive success in both sexes. To modulate these effects, females and males employed different strategies. However, they achieved their respective goals through a shared pathway: reducing negative effects for social bonds formed with smaller‐bodied males and enhancing positive effects for social bonds formed with larger‐bodied males. Our multivariate analysis of various aspects of avian reproduction suggests that the formation of social bonds plays a more important role than alternative reproductive strategies in determining individual reproductive success.